Enhancing Police Training and Competency Development through Modern Instructional Frameworks - Budi Susanto (Universitas Negeri Semarang, 2025)
Police training and competency development are central to ensuring effective, ethical, and accountable law-enforcement performance. As public expectations rise and the complexity of policing challenges increases, modern police agencies must adopt training frameworks that emphasize technical proficiency, communication skills, cultural awareness, and critical decision-making. This study examines the effectiveness of contemporary training models by combining survey data from 920 police officers, structured interviews with training instructors, and field observations at three police academies. Quantitative findings indicate that scenario-based training, de-escalation modules, and digital learning tools significantly improve officers’ operational readiness (p < 0.01). Qualitative results suggest that blended learning, mentorship structures, and continuous competency assessments enhance adaptability and long-term performance. Despite progress, challenges persist, including insufficient training time, uneven access to technological resources, and limited emphasis on emotional intelligence and community engagement. The study concludes that integrated, evidence-based training systems—combining pedagogical innovation, technological enhancement, and continuous evaluation—are essential for strengthening policing standards and improving public trust. This research contributes to policing science by providing a structured framework for competency-based training reform and aligning instructional practices with contemporary operational demands.